Perbandingan Efisiensi Media Pembuangan Sampah Organik Rumah antara Bak Sampah Sederhana dengan Lubang Biopori (Studi kasus : masyarakat Desa Nanggala, Kecamatan Cikeusik, Kabupaten Pandeglang) - Chaedar Alif Prada; Fathia Nurul Mujaddidah; Raven Daniel Martin; Anis Nurul Shofriyyah; Muhammad Nor Mahmudi; Yoan Kargy Hakim; Beatrice Immanuel Marampa; Regita Dian Astriana Prayitno; Prastowo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The waste management system carried out by the people of Kampung Benger, Nanggala Village is not yet good. This can be seen from the garbage thrown by the village community, not sorted between organic and non-organic waste. The increase in landfill without proper waste management is estimated to be the reason for not creating a clean environment. Most of the people of Kampung Benger still throw their trash into the gutter or burn it around the house, even though there is already a Temporary Disposal Site (TPS) in Nanggala Village. The purpose of this activity is to find more efficient and appropriate household organic waste disposal media to be applied in Nanggala Village. The more efficient and appropriate household organic waste disposal media to be implemented in Nanggala Village is by making 2 trash bins, each measuring 50 cm x 50 cm x 50 cm. Because when compared with making biopori holes as much as 1 piece per day, making 2 pieces of trash for more than two months is more effective and efficient. This can make it easier for residents to dispose of waste and do not spend much time when making it, compared to the time needed to make one biopori hole every day. Keywords: landfill, Nanggala Village, organic waste